Penyusunan Laporan Keuangan berdasarkan ISAK 35 - Eliyanora; Devi Indah Sari; Ferdawati (Politeknik Negeri Padang, 2022)
This study aims to show how a non-profit entity or non-profit organization such as a foundation in preparing financial statements. The foundation's financial statements are prepared in accordance with ISAK (Interpretation of Financial Accounting Standards) No. 35 where non-profit organizations must also prepare financial statements and report to users of financial statements. Based on ISAK 35 financial statements, it is necessary to prepare Statements of Financial Position, Statements of Comprehensive Income, Statements of Changes in Net Assets and Statements of Cash Flows by adjusting account naming according to ISAK 35. For the preparation of these financial statements, the help of Microsoft Excel is used. With this Excel program, the preparation of financial reports will be faster and more efficient, and the form of recording and reports can be made according to the needs of the entity.